Connectivity Analysis for Free-Flow Traffic in VANETs: A Statistical Approach. (28th October 2013) - Chen, Chen; Du, Xiaobo; Pei, Qingqi; Jin, Yanan
Abstract : Intervehicle communication gives vehicles opportunities to exchange packets within the limited radio range and self-organized in Ad Hoc manner into VANETs (Vehicular Ad Hoc Networks). However, due to issues such as the high mobility, insufficient market penetration ratio, and lacking of roadside units, connectivity is actually a big problem in VANETs. In addition, relying only on the direct connectivity in most of the previous works, say broadcasting which provides one-hop connections between nodes is far from the continuously growing application demands in VANETs, such as inter-vehicle entertainments, cooperative collision avoidances, and inter-vehicle emergency notifications. Therefore, the indirect connectivity from multihop forwarding is also a necessary complement especially for the case where direct connection is hardly achieved. In this paper, we define a new metric, that is, available connectivity, to consider both direct and indirect connectivity. After analyzing the statistical properties of direct and indirect connectivity in vehicular environment, the available connectivity is proposed and quantified for practical usage. Numerical results show that our available connectivity could provide correct and useful references for protocols design and performance improvements of different applications.